2011
DOI: 10.1111/j.1095-8649.2011.03072.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish response to the temporal hierarchy of the natural flow regime in the Daly River, northern Australia

Abstract: In this study, relationships between flow variation across multiple temporal scales and the distribution and abundance of three fish species, western rainbowfish Melanotaenia australis, sooty grunter Hephaestus fuliginosus and barramundi Lates calcarifer were examined at eight sampling reaches in the Daly River, Northern Territory, Australia. Discharge was highly seasonal during the study period of 2006-2010 with a distinct wet-dry discharge pattern. Significant catchment-wide correlations were identified betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
(88 reference statements)
1
41
0
Order By: Relevance
“…Large wet-season flows are likely to result in high recruitment pulses as a result of both high levels of spawning in the large wet-season flows, and higher juvenile survival as a result of the subsequent higher dryseason flows. For example, the recruitment strength of Barramundi and Sooty Grunter in the dry season is highly correlated to the preceding wet-season discharge (StauntonSmith et al 2004, Halliday et al 2008, Stewart-Koster et al 2011. However, significant water extraction could reduce dry-season discharge so that it is no longer correlated with the magnitude of the preceding wet season.…”
Section: Wet-dry Transition: Lowmediummentioning
confidence: 99%
“…Large wet-season flows are likely to result in high recruitment pulses as a result of both high levels of spawning in the large wet-season flows, and higher juvenile survival as a result of the subsequent higher dryseason flows. For example, the recruitment strength of Barramundi and Sooty Grunter in the dry season is highly correlated to the preceding wet-season discharge (StauntonSmith et al 2004, Halliday et al 2008, Stewart-Koster et al 2011. However, significant water extraction could reduce dry-season discharge so that it is no longer correlated with the magnitude of the preceding wet season.…”
Section: Wet-dry Transition: Lowmediummentioning
confidence: 99%
“…This may range from relatively complex models such as ours to relatively simple hierarchical models that adequately reflect the conceptual understanding of a system (Latimer et al 2006, Webb and King 2009, Stewart-Koster et al 2011. The complexity of the statistical model will depend on the characteristics of the data and the conceptual understanding of the system.…”
Section: Species' Abundance and The Importance Of Patch Quality And Cmentioning
confidence: 99%
“…Jowett & Biggs (2008) suggested that decisions on ecological flows should be made by identifying the valued biological components (e.g., specific taxa) and the components of flow regimes that are redundant with respect to these (i.e., that are not important for supporting the taxa). Similarly, responses of fishes to various components of the flow regime are also likely to differ between species and age classes (Stewart-Koster et al 2011). Clearly identifying the specific biological values to be supported helps to establish 'designer flow regimes' and is a pragmatic approach (Jowett & Biggs 2006).…”
Section: Discussionmentioning
confidence: 99%